(untitled) - Copeland, Thomas E. (New York, 2005)
This classic textbook in the field, now completely revised and updated, provides a bridge between theory and practice. Appropriate for the second course in Finance for MBA students and the first course in Finance for doctoral students, the text prepares students for the complex world of modern financial scholarship and practice. It presents a unified treatment of finance combining theory, empirical evidence and applications.
Keywords: Corporations; Finance